Autonomous Mobile Robots in Nature: Transfer RNAs in Escherichia coli Bacteria - Piros, Sandor (2008)
A Master of Science Thesis in Mechatronics Submitted by Sandor Piros Entitled, "Autonomous Mobile Robots in Nature: Transfer RNAs in Escherichia coli Bacteria" May 2008. Available are both Soft and Hard Copies of the Thesis.